Effect of body weight changes on hypertension in Indonesian adults (A 14-year follow up) - Mahwati, Yeni (UI Scholars Hub, 2019)
Background: Obesity is one of the major risk factors of hypertension. There is no large cohort study designed to investigate the quantitative association between body weight changes and the risk of hypertension in Indonesia. The aim of this study was to determine the impact of longitudinal BMI changes on hypertension in Indonesian adults. Methods: Body Mass Index (BMI) was computed by dividing weight (kg) by height squared (m2). Based on the BMI at baseline, the participants formed four weight-change groups: normal weight-maintainers, weight-gainers, weight-losers and overweight or obese-maintainers. The effect of age on the relationship between body weight changes and hypertension was analyzed by logistic regression models using stratified analysis. Results: Four body weight changes were identified: normal weight-maintainers (41.95%), weight-gainers (18.83%), weight-losers (5.24%), and overweight or obese-maintainers (33.98%). The stratified logistic regression analysis showed that changes in the relationships between the BMI changes and hypertension with age generally tended to be positive in the younger age-based subgroups but negative in the older subgroups. Relative to the normal weight-maintainers, the weight-gainers had the highest likelihood of hypertension (OR=1.68 95%CI [1.23-1.93]). Conclusions: The findings of the study underline the importance of maintaining normal weight for preventing hypertension especially for the middle-aged.